Kinematics of carbon stars in the outer regions of the Small Magellanic Cloud - Hatzidimitriou, D.; Croke, B. F.; Morgan, D. H.; Cannon, R. D. (1997)
We present a radial velocity survey of a sample of the field population of carbon stars in the outer parts of the Small Magellanic Cloud (SMC). This first set of results includes radial velocities for 71 carbon stars, with an individual precision of +/- 2-5 km/s. The mean heliocentric velocity of the stars (excluding one very high velocity star) is 149.3+/-3.0 km/s with a velocity dispersion of 25.2 +/- 2.1 km/s. These values drop to 145.5+/-2.7 km/s and 20.6+/-1.9 km/s respectively, if we exclude the stars belonging to the Outer Wing. The velocity distribution does not show the multiple peaks seen in some samples of Population I objects. The mass of the SMC as inferred from the above velocity dispersion (without the outer Wing stars) is ~= 1.2~10^9M_{\odot}. Tables 1a and 1b are available in electronic form at the CDS via anonymous ftp 130.79.128.5 or http://cdsweb.u-strasbg.fr/abstract.html
Keywords: GALAXIES: KINEMATICS; Magellanic Clouds; STARS: CARBON STARS